Assessment of human placental perfusion by intravoxel incoherent motion MR imaging. (17th January 2019) - Siauve, Nathalie; Hayot, Pierre Humbert; Deloison, Benjamin; Chalouhi, Gihad E.; Alison, Marianne; Balvay, Daniel; Bussières, Laurence; Clément, Olivier; Salomon, Laurent J.
Abstract: Purpose: To provide functional information on the human placenta, including perfusion, and diffusion, with no contrast agent injection, and to study correlations between intravoxel incoherent motion (IVIM) placental parameters and fetal growth. Materials and methods: MRI was performed in women undergoing legal termination of pregnancy at 17–34 weeks, including a 4-b-value and 11-b-value DW sequences. The apparent diffusion coefficient (ADC), the restricted diffusion coefficient (D), the pseudoperfusion coefficient (D*), and the perfusion fraction (f) were calculated. Their relationships with gestational age, Z-scores for fetal and placental weight were evaluated by means of regression analysis. Logistic regression analysis was used to assess the ability of IVIM parameters to predict/detect intrauterine growth retardation (SGA). Results: Fifty-five pregnant women, including nine cases of SGA (16%), were included in the study. The ADC ( n = 55) showed a quadratic correlation with gestational age ( p < .001) and a linear correlation with the fetal weight Z-score ( p = .02). Mean ADC values were significantly different between normally growing and SGA fetuses (2.37 ± 0.25 versus 2.29 ± 0.33 10 −3 .mm 2 .s −1, p =.048). The perfusion fraction f ( n = 23) showed a quadratic correlation with gestational age ( p = .017) and a linear correlation with the fetal weight Z − score ( p = .008). Mean f values differed significantly between normally growing and SGA fetuses (42.55 ± 9.30% versus 27.94 ± 8.76%, p = .002). The receiver operating characteristics (ROC) curve for f to predict SGA was produced (area under the ROC curve = 0.9). Conclusions: The observed association between f and fetal weight suggests that fMRI could be suitable for studying placental insufficiency and for identifying risk of SGA. Trial registration: ClinicalTrials.gov identifier: NCT01092949.